Depression is associated with heart failure in patients with type 2 diabetes mellitus - Chen, Yanying; Long, Chen; Xing, Zhenhua (Frontiers in Public Health, 2023)
Background Type 2 diabetes mellitus (T2DM) is associated with an increased risk of heart failure (HF). Depression, a common comorbidity of T2DM, may further increase the risk of heart failure (HF). We investigated the association between depression and incident HF in patients with T2DM. Methods and results Depressive symptoms were assessed in the ACCORD Health-Related Quality of Life study participants at baseline, 12, 36, and 48 months using the nine-item Patient Health Questionnaire (PHQ-9). The severity of depressive symptoms was categorized as none (0–4 points), mild (5–9 points), or moderate-severe (10–24 points). Cox regression with PHQ-9 as a time-dependent covariate was used to assess the association between depression and incident HF. During the median follow-up of 8.1 years, 104 participants developed HF (incidence: 7.1/1,000 person-years). Half of the participants with moderate-severe depression were relieved and a significant percentage of participants without depression or with mild depression worsened to mild or moderate-severe depression during the follow-up period, respectively. Each unit increase in the PHQ-9 score was associated with a 5% higher risk of HF (hazard ratio [HR]:1.05, 95% confidence interval [CI]: 1.01–1.10). Patients with depression ever (HR: 2.23, 95% CI: 1.25–3.98) or persistent depression (HR: 2.13, 95% CI: 1.05–4.44) had a higher risk of HF than those without depression ever. Conclusion Depressive symptoms change greatly in T2DM patients, depressive symptoms are an independent risk factor for HF. These results reinforce the importance of continuous evaluation and management of mental health status in T2DM patients with high HF risk.